Development of the Bogolyubov-Mitropolsky method of integral varieties - Lykova О. B. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A survey is presented of some results relating to the development of the Bogolyubov-Mitropol’skii method of integral manifolds.